Prognostic significance of neutrophil to lymphocyte ratio (NLR) in oral squamous cell carcinoma - Dineshkumar Thayalan; Nirmala Anandan; Krishnan Rajkumar; Indumathi N (Oral Oncology Reports)
Background: Tumor microenvironment is one of the evading research in the progression of cancers. Circulating neutrophils reflect the system's inflammatory response and study the growth of tumor cells thereby inducing cancer progression. Aim and objectives: The current study aims to evaluate the NLR ratio in oral squamous cell carcinoma group and to compare it with that of normal control and Premalignant group. Material and methods: This study is retrospective, the medical records of 48 OSCC patients, 48 Leukoplakia patients, and 48 normal healthy controls were taken. Association between NLR and clinicopathological variables were assessed. Tukey's post-hoc test was done to compare the variables. Kaplan Meier analysis was done for the analysis of overall survival. Results: The NLR ratio was assessed and compared between the three groups. The mean NLR ratio was found to be 3.79 in Oral squamous cell carcinoma patients, 2.62 in leukoplakia patients, and 2.07 in the normal control group. Conclusion: An increase in NLR levels was seen in OSCC patients. Increased NLR was also seen associated with advanced tumor staging and grading.